Work Practices and Challenges in Pull-Based Development: The Integrator's Perspective - Gousios, Georgios; Zaidman, Andy; Storey, Margaret-Anne; Van Deursen, Arie (2015 IEEE/ACM 37th IEEE International Conference on Software Engineering, 2015)
In the pull-based development model, the integrator has the crucial role of managing and integrating contributions. This work focuses on the role of the integrator and investigates working habits and challenges alike. We set up an exploratory qualitative study involving a large-scale survey of 749 integrators, to which we add quantitative data from the integrator's project. Our results provide insights into the factors they consider in their decision making process to accept or reject a contribution. Our key findings are that integrators struggle to maintain the quality of their projects and have difficulties with prioritizing contributions that are to be merged. Our insights have implications for practitioners who wish to use or improve their pull-based development process, as well as for researchers striving to understand the theoretical implications of the pull-based model in software development.